The effect of plant‐based diet and suboptimal environmental conditions on digestive function and diet‐induced enteropathy in rainbow trout (Oncorhynchus mykiss). (21st February 2017) - Mosberian‐Tanha, P.; Schrama, J.W.; Landsverk, T.; Mydland, L.T.; Øverland, M.
Abstract: This experiment investigated intestinal enteropathy and digestive function of rainbow trout challenged with soybean meal‐based diet (SBM) at optimal or suboptimal environments created by normal or reduced water flow, respectively. Oxygen level remained above 7 mg L ‐1 for optimal environment and between 4 and 5 mg L ‐1 for suboptimal environment. Triplicate groups of fish (mean body weight 74 g) were fed fishmeal‐based diet (FM) or SBM at optimal environment in period 1 (28 days). In period 2 (42 days), fish were subjected to a change from FM to SBM or remained on the same diet as used in period 1. The fish were also exposed to change from optimal to suboptimal environment or remained under optimal conditions. The fish subjected to change from FM to SBM, regardless of their environment, showed similar degree of enteropathy from day 14. Lipid and starch digestibility was lower in SBM‐fed fish at suboptimal environment compared to fish fed the same diet at optimal environment. Crude protein digestibility, however, was highest in SBM‐fed fish at suboptimal environment throughout period 2. In conclusion, in SBM‐fed rainbow trout, exposure to suboptimal environment did not change the degree of enteropathy; however, lipid and starch digestibility were further reduced.